Is Platonism life denying? - Motta, Guilherme Domingues da (Revista Archai, 2016)
The Phaedo contains a number of passages which could lead to the interpretation that Platonism is a denial of life. Such an interpretation could only be maintained by reading these passages out of context and also by ignoring a number of elements from other Plato’s texts. The first step to solve this problem is to stress that such statements about how desirable is death always concern the philosopher, whose model is the dialogues’ character, Socrates. This character was meticulously constructed to be regarded as someone extraordinary; a character who has undergone a process of “initiation” in which he acquired a philosophical dýnamis, namely, the capacity to recognize the existence and the value of the highest objects of knowledge, and also the pleasure of their contemplation. Considering that “death” in the Phaedo means only the separation of body and soul, a process in which soul is not annihilated, then it means the continuity of the contemplative life, which during the corporeal existence was hampered by the limits imposed by the body. Hence, life after death means a life of continuous enjoyment of the greater good and pleasure. But beyond that line of argument, it must be determined how Plato, in his dialogues, addressed the issue of the bodily pleasures for both the philosopher as well as for the common man. And, in this case, it is clear that Platonism is not a denial of life, but rather the affirmation of life, both in bodily dimension and spiritual.